Tanggung Jawab Pemerintah Daerah Terhadap Penggunaan Sepeda Listrik Di Kota Ambon - Sabanari, Irnayanti; Piris, Hendry John; Tita, Heillen M Y (Faculty of Law, Universitas Pattimura, 2024)
Technological development occurs in every field, one of which is the renewal from conventional bicycles to electric bicycles. Electric bicycles are regulated in Minister of Transportation Regulation Number PM 45 of 2020 concerning Certain Vehicles Using Electric Motor Drives. These regulations regulate the terms and conditions and routes for using electric bicycles. One of the provisions is that the user must be at least 12 years old, which is categorized as a child. Apart from that, what is regulated in the provisions for using electric bicycles is understanding and obeying traffic rules and using a helmet. However, in reality, electric bicycle users in Ambon City are not yet included in regional regulations